Refugee healthcare in Canada: responses to the 2012 changes to the interim federal health program. (2017) - Enns, Richard; Okeke-Ihejirika, Philomina; Kirova, Anna; McMenemy, Claire
From its inception in 1957, Canada's Interim Federal Health Program (IFHP) offered comprehensive healthcare coverage to refugees regardless of their status. In 2012, Canada's federal government introduced changes to the IFHP that differentiated between basic and expanded or supplemental levels of care, and coverage depending upon status. These changes were broadly opposed by many Canadians who feared that Canada was no longer meeting its healthcare obligations for refugees, and through a successful legal challenge in the Federal Court of Canada. The analysis presented here interrogates these changes against the international obligations assumed by the Government of Canada through ratification of international instruments since 1948 and national commitments contained in the 1982 Canadian Charter of Rights and Freedoms.